Determination of thermodynamic properties and phase transition temperatures of phenylbenzoate-based calamitic liquid crystals by inverse gas chromatography method - Cakar, Ayse Erdogan; Cakar, Fatih; Ocak, Hale; Karavelioglu, Selvi; Eran, Belkiz Bilgin; Cankurtaran, Ozlem (TAYLOR & FRANCIS LTD, 2023)
In this study, Phenylbenzoate-based calamitic liquid crystals (LCs) were synthesized and characterized, and then the thermodynamic properties and phase transition temperatures were investigated by inverse gas chromatography (IGC) at infinite dilution. The phase transition temperatures of the LCs were determined in the range of 40-170 degrees C by the IGC method. Finally, in the thermodynamic equilibrium region (the range of 160-200 degrees C), Flory-Huggins theory and the equation of state theory with the LC-solvent interaction parameters, the effective exchange energy parameters, the weight fraction activity coefficient, and also the partial molar heat of mixing at infinite dilution of solvent, the molar heat of vaporization of solvent, and the partial molar heat of sorption of solvent were calculated.
Keywords: Liquid crystal; Inverse gas chromatography; phase transition temperature; thermodynamic properties; 2ND VIRIAL-COEFFICIENTS; IMPERFECTION; PARAMETERS; MIXTURES; POLYMER; ETHER; IGC; Crystallography; Physics